Structural Health Monitoring Method of Pantograph–Catenary System Based on Strain Response Inversion - Liu, Sheng; Wei, Yibo; Yin, Yongxin; Feng, Tangzheng; Lin, Jinbao (Frontiers in Physics, 2021)
Pantograph-catenary system provides electric energy for the subway lines; its health status is essential to the serviceability of the vehicle. In this paper, a real-time structural health monitoring method based on strain response inversion is proposed to calculate the magnitude and position of the dynamic contact force between the catenary and pantograph. The measurement principle, calibration, and installation detail of the fiber Bragg grating (FBG) sensors are also presented in this paper. Putting this monitoring system in use, an application example of a subway with a rigid overhead catenary is given to demonstrate its performance. The pantograph was monitored and analyzed, running underground at a maximum speed of 80 Km/h. The results show that the strain response inversion method has high measurement accuracy, good data consistency, and flexibility on sensor installation. It can accurately calculate the magnitude and location of the contact force exerted on the pantograph.